Desordens temporomandibulares em crianças e adolescentes - Ikeda, Tarcísio Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The purpose of this text is evaluate some aspects related to temporomandibular joint disorder in children and teenagers, like as a etiology, diagnosis and treatment, emphasizing the importance of the adequate diagnosis in a growth phase and of development craniofacial and of the muscles of the mastication. DTMs may present problems that involves the temporomandibular joint, mastication muscles and adjacent structures. Usually in children those symptoms are present in a smaller intensity than in adults, To avoid symptoms development premature diagnosis is advisable. The a etiology of TMD in pediatric patient and teenagers is multifatorial, among the etiological factors, the most mentioned are: systemic conditions, occlusal factors, traumas and psychological alterations related to muscles hyperactivity. TMD is a pathologic condition in which a stomatognatic system dysfunction exists, that could be involved mastication muscles (muscular disorders), TMJ (articular disorders), or both. Muscular disorders, could involve the masticatory, head or neck muscles; Articular disorders is characterized by internal disturbances of the temporomandibular joint and muscular-articular when involves musculature and TMJ

Esse trabalho tem como objetivo abordar os aspectos relacionados às desordens temporomandibulares (DTM) em crianças e adolescentes, como etiologia, diagnóstico e tratamento ressaltando a importância do diagnóstico correto uma vez que esses pacientes estão em fase de crescimento e de desenvolvimento craniofacial e dos músculos da mastigação. As DTMs apresentam problemas que envolvem a articulação temporomandibular, músculos da mastigação e estruturas adjacentes. Em crianças esses sintomas estão presentes em uma intensidade menor do que em adultos, por isso há se a necessidade de se fazer um diagnóstico precoce, procurando-se evitar sua evolução. A etiologia dessa síndrome em pacientes pediátricos e adolescentes é de ordem multifatorial dentre os quais os fatores mais citados são: sistêmicos, fatores oclusais, traumas e psicológicos relacionados com hiperatividade. A DTM constitui uma condição na qual existe uma desarmonia no sistema estomatognático, podendo ocorrer envolvimento dos músculos da mastigação, a ATM, ou ambos. Podem ser divididas em desordens musculares, quando acometem apenas a musculatura mastigatória e do pescoço; articulares, caracterizada por distúrbios internos da articulação temporomandibular e músculo-articulares quando acometem a musculatura e a articulação
Keywords: Transtornos da articulação temporomandibular; Articulação temporomandibular; Assistência odontológica para crianças; Temporomandibular Joint Disorders